Paradoks Pilihan Kebijakan Upah Minimum dalam konteks Politik Pembangunan Berbasis Efesiensi dan Pertumbuhan Ekonomi - Rusdi, Muhammad (Universitas Brawijaya, Indonesia, 2008)
Problems related to the process of minimum wage policy change in South Sulawesi always peep out debate and conflict which sometimes do not express what the desire of coalition advocacy, especially between trade union and Apindo. The purpose of this article is to describe, analyze and interprete some factors applied by policy subsystem both as resources and constraints in the choice process of nominal UMP 2006, advocacy coalitions 'policy resources to push the UMP policy change and the policy broker's strategy to mediate the conflict in the policy subsystem. The context of minimum wage policy subsystem, which consist of the Trade Union (SB), Association of Entrepreneur (Apindo), the government and the team of experts. Apindo's belief system is how to increase the production, labor's productivity and efficiency; while SB is important component in the production process. The other aspects showed that internal and external factors of the minimum wage policy in South Sulawesi including institutional aspects, existences and amounts of the coalition's members, and also their solidarity. Meanwhile, the external factors including the implementation of decentralization, mass media roles as well as the fluctuation of the economic condition, like inflation rate. In the context of UMP policy, SB and 4pindo as coalition advocacy have policy resources to influence the UMP policy makers. Its involve ability of the policy subsystem, lobby mechanism, and also authority which they have.